Mating-type distribution and fertility status in Magnaporthe grisea populations from Argentina - Consolo, Verónica Fabiana (2005)
Isolates of Magnaporthe grisea causing gray leaf spot on rice were collected in Argentina and analyzed for mating distribution and fertility. One hundred and twenty-five isolates of M. grisea were collected from rice plants between 2000 and 2003. Each isolate was tested for mating type through a polymerase chain reaction based assay. All M. grisea isolates from Argentina belonged to a single mating type, MAT1.1. The fertility status of isolates was determined using controlled crosses in vitro, pairing each isolate with GUY11 and KA9 (MAT1.2 standard hermaphroditic testers). Production of perithecia was scarce among isolates of the blast pathogen since a low percentage of them (7.2%) developed perithecia with only one of the fertile tester (KA9); all crosses failed with the other tester strain. Asci and ascospores were not observed. The presence of only one mating type and the absence of female fertile isolates indicate that sexual reproduction is rare or absent in M. grisea populations associated with rice in Argentina.